2019
DOI: 10.21608/zvjz.2019.12216.1036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Experimental Clostridium perfringens Infection on Some Immunological, Hematological and Biochemical Values in Broiler Chickens

Abstract: This study aimed to demonstrate the effect of Clostridium perfringens (Cl. perfringens) infection on broiler chickens. Also, to compare between the effect of amoxicillin and / or organic acids on Cl. perfringens infection through the evaluation of hemogram, blood chemistry, hepato-renal functions and immune response using ELISA technique. One hundred, one-day old Hubbard chicks were divided into five equal groups. Group 1: negative control, Group 2: infected broilers with Cl. perfringens type A (1.9×10 9 organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The appeared clinical signs in the infected group may be attributed to disturbance in the metabolic activity in liver caused by Clostridium toxins as recorded previously by Johansson, (2006) and Saleh et al (2011). Although, in the infected-treated chickens milder clinical symptoms and lower mortality rates appeared which might be related to efficacy of EOs and OAs blends either alone or in combination in controlling of necrotic enteritis as previously proved (Eid et al, 2018;Khodary et al, 2019;Pham et al, 2020;Kumar et al, 2021).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The appeared clinical signs in the infected group may be attributed to disturbance in the metabolic activity in liver caused by Clostridium toxins as recorded previously by Johansson, (2006) and Saleh et al (2011). Although, in the infected-treated chickens milder clinical symptoms and lower mortality rates appeared which might be related to efficacy of EOs and OAs blends either alone or in combination in controlling of necrotic enteritis as previously proved (Eid et al, 2018;Khodary et al, 2019;Pham et al, 2020;Kumar et al, 2021).…”
Section: Discussionsupporting
confidence: 70%
“…The hyperglobulinemia is mainly due to the bacterial septicemia that lead to lymphocyte stimulation, and differentiation into T and B types resulting in increase of globulins levels and acquired immune response (Coles, 1986). Also, Salah et al (2015) and Khodary et al (2019) reported a significant increase in the serum total protein and globulin levels in C. perfringens-infected chickens. In contrast, El-Sheikh et al (2018) reported that there was a significant decrease in serum levels of globulins in C. perfringensinfected chickens.…”
Section: Discussionmentioning
confidence: 90%
“…Similar findings by Abudabos et al (Abudabos et al, 2018;Abudabos & Yehia, 2013) dressing percentage and feed intake at the third week. Moreover, other studies (Elbayoumi et al, 2014) have reported that the groups challenged with C. perfringens were the most affected in their average weekly body weight and FCR during the first week of postinfection, while the groups treated with the antibiotics showed improved body weight and FCR. The results of TWG from zero to fifth week were in line with those obtained by Miller et al, 2010, who stated that the greater weight gains were recorded from 0 to 35-day period in all the bird groups treated with phages compared to the challenged control.…”
Section: Discussionmentioning
confidence: 82%
“…The live body weight (BW) was monitored weekly to calculate body weight gain (WG). The feed conversion ratio (FCR) was calculated as reported by Elbayoumi et al, 2014. Also, dead birds in each group were recorded daily to calculate the mortality rate as described by Miller et al, 2010, and European Broiler Index (EBI) was estimated as described by Mathis et al, 2016.…”
Section: Measurement Of the Growth Performancementioning
confidence: 99%
“…In the present study, broiler chickens treated with ampicillin and DMZ improved RBC count, hemoglobin concentration, PCV% and WBC count. In a previous study, amoxicillin administration in broiler chickens revealed beneficial efficacy against clostridial infections and enhanced the hematological variables (Khodary et al, 2019).…”
Section: Discussionmentioning
confidence: 86%